Windows Server 70-742 : Identity with Windows Server 2016 : complete video course - Alderman, Brian (LiveLessons (Indianapolis, Ind.), 2017)
Windows Server 70-742: Identity with Windows Server 2016 Complete Video Course covers the five objective domains for the Windows Server 70-742 exam. You learn concepts and see live demonstrations on how to complete administrative tasks associated with Windows Server 2016. Whether you’re new to Windows Server 2016 Identity Services or preparing to take the Microsoft Windows Server 70-742 exam, this course is designed for you. In this course, you learn how to install, configure, and manage the different services associated with identities in Windows Server 2016, including Active Directory, Group Policies, Certificate Services, and Rights Management Services. You also explore the different post-installation tasks, including configuration of domains and forests; management of users, computers, groups, and organizational units; and configuration of group policies. Throughout each lesson, trainer and author Brian Alderman works on virtual machines in a lab environment, as you probably will in preparation for the exam. Follow along to get hands-on experience with these tools. The more time you spend actually working with Active Directory in Windows Server 2016, the better your chances will be of passing the exam.